5-aminolevulinic acid photodynamic therapy for condyloma acuminatum of urethral meatus. (3rd October 2019) - Xie, Jiajia; Ao, Chunping; Li, Junpeng; Jiang, Lifen; Liu, Hui; Zeng, Kang
Abstract: Objectives: Condyloma acuminatum are the most common sexually transmitted diseases worldwide, and they are closely associated with human papillomavirus (HPV) infection. Urethral meatus is one of the places that warts occur. Many treatments for uretheral warts have limitations. In this study, we performed 5-aminolevulinic acid-photodynamic therapy (ALA-PDT) on patients and investigated the effectiveness of reducing HPV viral loads. Materials and Methods: In our study, 21 patients diagnosed with urethral condyloma acuminatum were included. After 4 h treatment of ALA, patients received PDT. Each patient received HPV test before every PDT cycle. The frequency of PDT was dependent on viral load changes. Results: All patients achieved complete clinical remission after the last session of ALA-PDT. There were significant differences in HPV viral loads between pretherapy and after one or three rounds of PDT treatment. Conclusions: ALA-PDT is a safe and effective method for treatment of condyloma acuminatum in urethra meatus. Dynamic monitoring of HPV viral loads can more objectively demonstrate the effectiveness and guide the treatment of PDT.